Analisa Perbandingan Metode MOORA, Promethee, dan Weighted product dalam Penentuan Lokasi Usaha - Tika Aenun Nadila; Septi Andryana; Ira Diana Sholihati (KITA Institute, 2021)
In building a business, there are many aspects that need to be considered in choosing the right business location,Â to minimize costs while still providing quality space to provide long-term benefits This research uses the Moora (Multi-objective optimize on the basis of ratio analysis) method, Promethee (Preference ranking organization method for enrichment evaluation), and Weighted product. These three methods were analyzed by manual calculation, then comparisons were made based on the effectiveness in processing the data and the level of conformity. The results showed that the suitability level of the weighted product method was higher with a value of 99.99857%, followed by MOORA 99.99779% and Promethee 99.99679%. Weighted products also have a fast and effective process stage, so this method is the method used in implementing web-based business location decision support systems . The results of manual and system calculations on weighted products also have the same results, namely the HI shop alternative with a value of 0.189 as the highest alternative.